1991
DOI: 10.1111/j.1365-2826.1991.tb00295.x
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine Content of the Stalk‐Median Eminence and Hypothalamus in Adult Female Sheep as Affected by Daylength

Abstract: In the ewe, plasma luteinizing hormone and prolactin concentrations exhibit seasonal variations. During long days, inhibition of pulsatile luteinizing hormone secretion is mediated by monoamines. In a model of ovariectomized ewes bearing a subcutaneous oestradiol implant, we previously showed that the steroid-dependent inhibition of luteinizing hormone involves the A15 dopaminergic nucleus of the retrochiasmatic area. In the present work, we compared the aminergic activities of tele-diencephalic structures in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

1992
1992
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 35 publications
1
22
1
Order By: Relevance
“…In the current study, we have shown that salsolinol is present in the IN/ME of lactating ewes. A higher concentration of salsolinol and its variability found in the anterior than the posterior part of the IN/ME suggest that the main source of this compound may be the dopaminergic cells from the IN A12 and/or these from the retrochiasmatic area (Thiery 1991). Our data did not show, however, a direct proof for salsolinol synthesis in these dopaminergic nuclei.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…In the current study, we have shown that salsolinol is present in the IN/ME of lactating ewes. A higher concentration of salsolinol and its variability found in the anterior than the posterior part of the IN/ME suggest that the main source of this compound may be the dopaminergic cells from the IN A12 and/or these from the retrochiasmatic area (Thiery 1991). Our data did not show, however, a direct proof for salsolinol synthesis in these dopaminergic nuclei.…”
Section: Discussioncontrasting
confidence: 53%
“…Because of the different localization of dopaminergic nuclei in the ovine hypothalamus (Thiery 1991), the statistical analysis for salsolinol was done separately for the anterior (nZ4) and posterior (nZ6) parts of the IN/ME, while the changes in the concentrations of prolactin and GH were analyzed together (nZ10) due to the same protocol of the experiment used for all ewes. The effect of suckling on salsolinol concentration was first examined by ANOVA for repeated measurements and then for consecutive perfusates by one-factor ANOVA followed by the Tukey's post hoc test (Statistica, StatSoft, Inc., Tulsa, OK, USA).…”
Section: Discussionmentioning
confidence: 99%
“…Several arguments suggest that these terminals are implicated in one of the final steps of the long-day-induced inhibition of LH secretion. Indeed, ME dopamine content and tyrosine hydroxylase (rate-limiting enzyme of the catecholamine biosynthesis) activity are lower under short days (high LH secretion) than under long days (low LH secretion; Thiéry 1991, Viguié et al 1996, 1997. Importantly, blockade of dopamine synthesis in the ME, by local infusion of -methyl-para-tyrosine ( MPT, a competitive tyrosine hydroxylase inhibitor) induces a stimulation of LH secretion in long day-inhibited OVX+E ewes (Viguié et al 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to stimulatory short days resulted in decreased dopaminergic activity in the median eminence as assessed both by a reduction in dopamine content and in TH activity [62,72]. No effect of short-day exposure on noradrenaline content in this structure or on TH activity in the other hypothalamic areas investigated was found [72].…”
Section: Sites Of Action Of Melatoninmentioning
confidence: 92%